The Secular Mind - Coles, Robert (Book collections on Project MUSE., 2001)
Does the business of daily living distance us from life's mysteries? Do most Americans value spiritual thinking more as a hobby than as an all-encompassing approach to life? Will the concept of the soul be defunct after the next few generations? Child psychiatrist and best-selling author Robert Coles offers a profound meditation on how secular culture has settled into the hearts and minds of Americans. This book is a sweeping essay on the shift from religious control over Western society to the scientific dominance of the mind. Interwoven into the story is Coles's personal quest for understand.